THE ESSENCE OF AGRICULTURE ENTERPRISES’ MARKETING RISKS - Писаренко, В. В.; Лях, Я. Ю. (Scientific Progress & Innovations, 2014)
The article presents defining and consideration of the essence agriculture enterprises’ marketing risks. There are have studied sources of marketing risks agriculture enterprises in the Ukrainian contemporary environment. Authors have proposed the classification of marketing risks agriculture enterprises. It is useful for edification and analyst of marketing risks during their management, in edition it is useful for adequate accepting risks by an enterprise, minimizing their negative implications, wide overegging areas of their arising.